MMP19 is upregulated during melanoma progression and increases invasion of melanoma cells - Müller, Matthias; Beck, Inken M; Gadesmann, Judith; Karschuk, Nadine; Paschen, Annette; Proksch, Ehrhard; Djonov, Valentin; Reiß, Karina; Sedlacek, Radislav (Modern pathology, 2010)
During the progression of cutaneous melanomas, matrix metalloproteinases (MMPs) facilitate the tumour cells to traverse the basement membrane and invade the dermis. In this study, we analysed the expression of MMP19 in the course of melanoma progression. Although MMP19 was absent in melanocytes and melanoma cells of early stages of melanoma development, its expression was strongly upregulated in the neighbouring keratinocytes that may facilitate the vertical outgrowth of melanoma cells. In contrast to early stages, MMP19 was upregulated during the vertical growth phase of melanoma and in metastases. The upregulation of MMP19 in melanoma of Clark levels IV and V correlates with that of MMP2 and also simultaneously with ceased expression of E-cadherin. To reveal whether MMP19 facilitates the invasion of melanomas, we examined adhesion and migratory capacity of selected melanoma cell lines. Melanoma cell lines with low expression of MMP19 exhibited increased adhesion to various substrates and lower migration in comparison with the cell line with higher expression of MMP19. Moreover, ectopic expression of MMP19 could restore the migratory capacity of melanoma cells with low endogenous level of MMP19. These results suggest that the increase of MMP19 expression hallmarks the progression of cutaneous melanoma and might augment melanoma growth by promoting the invasion of tumour cells.
Gesehen am 10.05.2023